-8(y+5)=9y+11

Simple and best practice solution for -8(y+5)=9y+11 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -8(y+5)=9y+11 equation:


Simplifying
-8(y + 5) = 9y + 11

Reorder the terms:
-8(5 + y) = 9y + 11
(5 * -8 + y * -8) = 9y + 11
(-40 + -8y) = 9y + 11

Reorder the terms:
-40 + -8y = 11 + 9y

Solving
-40 + -8y = 11 + 9y

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '-9y' to each side of the equation.
-40 + -8y + -9y = 11 + 9y + -9y

Combine like terms: -8y + -9y = -17y
-40 + -17y = 11 + 9y + -9y

Combine like terms: 9y + -9y = 0
-40 + -17y = 11 + 0
-40 + -17y = 11

Add '40' to each side of the equation.
-40 + 40 + -17y = 11 + 40

Combine like terms: -40 + 40 = 0
0 + -17y = 11 + 40
-17y = 11 + 40

Combine like terms: 11 + 40 = 51
-17y = 51

Divide each side by '-17'.
y = -3

Simplifying
y = -3

See similar equations:

| (3t^2+9)(3t^2+9)= | | f(x)=x^2+6x+4 | | 57*(4p)=228 | | y-5+1=6 | | 6-3(-4-3x)=90 | | 128x=x | | 4x^3/x=0 | | 43+x=x | | 6y-16=-4(y-6) | | 200+(.75*1000)= | | .1036*(1/.1036)=18 | | 0.2(x+5)+1.2(x-4)= | | 43x=x | | 0.1818181818= | | -10x^2=50x | | t^2-23+52=-50 | | -5+n=-44 | | (3x+2y)(6x-4y)=0 | | X-59=6(2x+3)-11 | | (2m^2+4m+5)(5m-4)= | | -3+n=37 | | d*3.141/0.136=18 | | -4(0.1x+0.5)-0.9=-0.5 | | -2(x+3)+11=11-3x | | d*3.141/.1036=18 | | 8+n=41 | | 5(-8n+1)=85 | | 8(x+1)+10x=9 | | (2x-9)(5x+4)= | | 7=15-Y | | X+44=3x-42 | | (d*3.141)/.1036=18 |

Equations solver categories